不同产地文冠果种仁黄酮类成分的LC-MS/MS检测LC-MS/MS detection of flavonoids in Xanthoceras sorbifolum Bunge kernel from different origins - 姜鑫，房安石，杜维，阮成江 JIANG Xin, FANG Anshi, DU Wei, RUAN Chengjiang (Zhongguo youzhi, 2023)
为考察不同产地文冠果种仁黄酮类成分的差异，以山东潍坊的60份和辽宁大连的58份文冠果种仁为原料，采用LC-MS/MS法检测其黄酮类成分及含量，并对两地文冠果种仁黄酮类成分含量的差异进行了对比分析。结果表明：118份文冠果种仁中均检测出5种黄酮类成分，其中芦丁含量为1.422~40.704 μg/g，表没食子儿茶素含量为2.513~6.406 μg/g，没食子儿茶素没食子酸酯含量为1.994~4.574 μg/g，二氢槲皮素含量为1.102~4.452 μg/g，没食子儿茶素含量为0.806~4.057 μg/g；两地文冠果种仁黄酮类成分含量大小依次为芦丁>表没食子儿茶素>没食子儿茶素没食子酸酯>二氢槲皮素>没食子儿茶素；山东潍坊不同样树种仁中黄酮类成分总含量介于10518~25.445 μg/g之间，样树WF927的黄酮类成分总含量最高；辽宁大连不同样树种仁中黄酮类成分的总含量介于8.347~52.087 μg/g之间，样树DL392的黄酮类成分总含量最高；两地文冠果种仁黄酮类成分含量间差异显著，其中辽宁大连文冠果种仁中黄酮类成分总含量平均值（19491 μg/g）极显著高于山东潍坊的（16.320 μg/g）;两地118份文冠果种仁中，黄酮类成分总含量最高的为DL392（52.087 μg/g）、DL395（43.711 μg/g）和DL347（40.481 μg/g）。 In order to investigate the changes of flavonoids in Xanthoceras sorbifolium Bunge kernels from different origins, 60 samples from Weifang, Shandong province and 58 samples from Dalian, Liaoning province were used as raw materials, and the flavonoids composition and contents were detected by LC-MS/MS method, and the differences of flavonoids content from two origins were compared and analyzed. The results showed that 5 kinds of flavonoids were detected in 118 Xanthoceras sorbifolium Bunge kernels, among which the content of rutin was 1.422-40.704 μg/g, the content of epigallocatechin was 2.513-6.406 μg/g, the content of gallocatechingallate was 1.994-4.574 μg/g, the content of dihydroquercetin was 1.102-4.452 μg/g, and the content of gallocatechin was 0.806-4.057 μg/g. Rutin content was the highest, followed by epigallocatechin, gallocatechingallate, dihydroquercetin and gallocatechin. The total flavonoids content of kernels from Weifang, Shandong province was between 10518 μg/g and 25.445 μg/g, and the total flavonoids content of WF927 was the highest, the total flavonoids content of kernels from Dalian, Liaoning province was between 8.347 μg/g and 52.087 μg/g, and the total flavonoids content of DL392 was the highest. The content of flavonoids was significantly different between two origins. The average total flavonoids content in Xanthoceras sorbifolum Bunge kernel from Dalian, Liaoning province (19.491 μg/g) was significantly higher than that from Weifang, Shandong province(16.320 μg/g). 118 Xanthoceras sorbifolium Bunge kernel from two origins had the highest total content of flavonoids in DL392 (52.087 μg/g), DL395 (43.711 μg/g) and DL347 (40481 μg/g).